A Splitting Iteration Method for Double $X_0$-Breaking Bifurcation Points (Journal of Computational Mathematics, 1998)
A splitting iteration method is proposed to compute double $X_0$-breaking bifurcation points. The method will reduce the computational work and storage, it converges linearly with an adjustable speed. Numerical computation shows the effectiveness of splitting iteration method.
Keywords: Double $X_0$-breaking bifurcation point; splitting iteration method; extended system.